Computational modeling of interfacial behaviors in nanocomposite materials. (1st June 2017) - Lin, Liqiang; Wang, Xiaodu; Zeng, Xiaowei
Abstract: Towards understanding the bulk material response in nanocomposites, an interfacial zone model was proposed to define a variety of material interface behaviors (e.g. brittle, ductile, rubber-like, elastic-perfectly plastic behavior etc.). It also has the capability to predict bulk material response though independently control of the interface properties (e.g. stiffness, strength, toughness). The mechanical response of granular nanocomposite (i.e. nacre) was investigated through modeling the "relatively soft" organic interface as an interfacial zone among "hard" mineral tablets and simulation results were compared with experimental measurements of stress-strain curves in tension and compression tests. Through modeling varies material interfaces, we found out that the bulk material response of granular nanocomposite was regulated by the interfacial behaviors. This interfacial zone model provides a possible numerical tool for qualitatively understanding of structure-property relationships through material interface design.